Microwave vitrification of uranium-contaminated soil for nuclear test site and chemical stability. Issue 10 (July 2019) - Chen, Shunzhang; Shu, Xiaoyan; Tang, Hexi; Mao, Xueli; Xu, Chen; Lu, Xirui
Abstract: In early days, nuclear tests had left plenty of radionuclide-contaminated soil over the world and disposal of which is vital to human health. In this work, vitrification technology was employed to achieve the immobilization of radionuclide. It was demonstrated that three kinds of simulated uranium contaminated soil for nuclear test site (Gray desert soil, Saline-alkali soil and Aeolian sandy soil) could be successfully vitrified within 30 min without any additional components via microwave sintering. All the uranium contaminated soil became amorphous at 1300 °C. Uranium was considered to be surrounded by aluminium silicate glass network structure, and three kinds of 50000 μg/g uranium concentration sintered soil samples presented reliable chemical durability. In addition, the ultimate solubility of uranium and chemical stability of different sintered soil samples were affected by the content of their components.